Preparation and enhancement of mullite reticulated porous ceramics for porous media combustion. Issue 17 (1st December 2019) - Liang, Xiong; Li, Yawei; Pan, Liping; Sang, Shaobai; Zhu, Tianbin; Li, Benwen; Aneziris, Christos G.
Abstract: The insufficient strength and thermal shock resistance of mullite reticulated porous ceramics (RPC) limited their application in porous media combustion. To strengthen mullite RPC, the struts with three layers were prepared using the combined approaches of polymeric replica and vacuum infiltration. The effects of residual stress within the struts on thermal shock resistance of mullite RPC were investigated by finite element analysis (FEA). The results showed that the strut was composed of the coating of reaction-bonded mullite, middle layer of mullite skeleton and the triangular filling layer. The triangular voids and surface cracks were eliminated in the formed struts, resulting in a higher strength of mullite RPC than that of hollow strut. In addition, FEA results indicated that the residual compressive stress formed in the coating of strut after mullite RPC was sintered at 1450 °C and 1500 °C, while the residual tensile stress formed at 1550 °C. The larger residual compressive stress within the strut coating was beneficial to enhance the thermal shock resistance of mullite RPC.